Association Rules Mining in Cloud Computing Environments using Improved Apriori Algorithm - Sharma, Avinash; dixit, Sarvottam; Tiwari, NK (International Journal of Computer Sciences and Engineering, 2018)
This paper describes how data mining is used in cloud computing. Data Mining used for extracting potentially useful information from raw data. The integration of data mining techniques into normal day-to-day activities has become commonplace. Every day people confronted with targeted advertising, and data mining techniques help businesses to become more efficient by reducing costs. Cloud computing provides a powerful, scalable and flexible infrastructure into which one can integrate, previously known, techniques and methods of Data Mining. Data security and access control are the most challenging in cloud computing because users send their sensitive data to the cloud service providers. The service providers must have a suitable way to protect their client’s sensitive data. Association rules are dependency rules, which predict occurrence of an item based on occurrences of other items. Apriori is the best-known algorithm to mine association rules. In this paper, we use Modified Apriori algorithm to mine the data from the cloud using sector/sphere framework with association rules.